Using Reflective Thinking to Find the Best Solutions to Combinatorics Problems - Ahsan, Muhammad; Ibrahim, Abdullah; Mappanyompa, Buhaerah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
This research explores the reflective thinking process in solving combinatorial problems to achieve optimal solutions. Seventy students who have taken or are taking combinatorial courses participated in this study. The research procedure includes selecting suitable participants, distributing combinatorial questions that have been tested for quality to ensure validity and reliability, and conducting tests. After the test, interviews were conducted with several randomly selected students. Data from tests and interviews were analyzed based on reflective thinking indicators. This study uses several instruments, such as the Myers-Briggs Type Indicator and the Matching Familiar Figures Test, to identify students' reflective thinking characteristics and tendencies. Data analysis includes analyzing the results, comparing the results between reflective students for each instrument, and formulating conclusions. The results showed that reflective thinking helped students evaluate their strategies, identify mistakes faster, and adjust approaches based on new understandings gained from reflection. This approach has proven effective in supporting more creative and systematic problem-solving and helping achieve optimal solutions according to research objectives.